Efektivitas Quantum Channel dalam Mekanisme Transmisi Kebijakan Moneter: Studi Kasus Indonesia Tahun 1993-2005 - Hirawan, Fajar Bambang (UI Scholars Hub, 2007)
In the year 2002, Y. V. Reddy introduced a new thought in monetary economics theory, especially about transmission mechanism of monetary policy. Reddy classified the channels of transmission mechanism into three types, there are quantum channel, interest rate channel, and asset price channel. Quantum channel consists of two channels, there are money channel and credit channel. This research will examine the differences between money channel and credit channel, the factors which affect volume of money supply (M2) and credit, the stability of quantum channel, and also effectiveness of quantum channel, especially related on its role to push the economic growth. This research uses a monthly data from the year 1993 until 2005. The analysis of this research divided into three parts of period, pre-crisis period (1993-1996), crisis period (1997-2001), and post-crisis period (2002-2005). In the pre-crisis period, credit channel more stable in transmission mechanism of monetary policy and more effective to push the economic growth. In the crisis, quantum channel did not effective to push economic growth. In the post-crisis period, quantum channel also did not effective to push the economic growth.